Mooch the messy meets Prudence the neat - Sharmat,Marjorie,Weinman; Sharmat,Marjorie,Weinman (New York Coward,mcCann & Geoghegan, 1978)
A messy rat named Mooch meet his very neat neighbor Prudence,and they learn about friendship and differences